Calculation and Analysis of DC Link Capacitor’s Current for AC-DC-AC Inverter - LIU Haitao; CHEN Tao (Kongzhi Yu Xinxi Jishu)
In order to guarantee the performance of converter, it needs to select the appropriate intermediate DC support capacitor. According to the analysis of the circuit topology and the switch modulation mode of converter and referring to the existing literature, it summerizes a method to calculate current of the capacitor. The theory and simulation results demonstrate that this method has good accuracy.